Rozvoj přípojek FTTx - Lafata, Pavel; Vodrážka, Jiří (International Society for Science and Engineering, o.s., 2010)
This paper describes the koncept of FTTx optical lines, the analysis of their current expansion and the estimation for the incoming years. The triple play services are often mentioned together with the FTTx lines. The fully functional workplace of passive optical network was built at the Department of Telecommunication Engineering, FEE, CTU in Pratur. This article also contains the description of this workplace and an example of its possible configuration.

Tento článek obsahuje popis koncepce optických přípojek FTTx, analýzu jejich současného rozšíření a krátkodobý výhled vývoje počtu řípojek v nejbližších letech. V souvislosti s optickými přípojkami jsou často zmiňovány i tzv. službytriple play. Vzhledem k tomu, že na Katedře telekomunikační techniky, FEL, ČVUT v Prazebylo vybudováno plně funkční pracoviště pasivních optických přístupových sítí, bude v tomto příspěvku popsána ukázka jejich možné konfigurace a využití.
Expansion of FTTx Lines